Analisis Framing Berita Nasional Kompas.com dan Lokal Lombokpost.jawapos.com dalam Pemberitaan Kasus Juliana WNA Brasil di Rinjani - Desak Putu Adistya Andini; Rieka Yulita Widaswara; I Nengah Putra Kariana (MUKASI: Jurnal Ilmu Komunikasi, 2025)
The death of Juliana Marins, a Brazilian national who fell while hiking Mount Rinjani, received widespread attention from both national and local media, each presenting the event with different framing approaches. This study aims to analyze the news framing of Kompas.com (national media) and Lombokpost.jawapos.com (local media) using a qualitative descriptive method and Robert N. Entman’s framing theory, which includes four elements: defining problems, diagnosing causes, making moral judgments, and suggesting remedies. Eight articles published between June 21 and July 1, 2025, were analyzed to examine differences in perspective. The results show that Kompas.com framed the event from a structural and formal viewpoint, emphasizing institutional roles and critiques of safety procedures. In contrast, Lombokpost.jawapos.com highlighted emotional aspects and human interest stories, focusing on the local guide’s account and volunteer efforts. These differences reflect each media’s editorial orientation and geographical proximity. The study affirms that media framing is influenced by social context, institutional positioning, and narrative strategies toward audiences.